2009
DOI: 10.2165/0023210-200923010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawing Benzodiazepines in Primary Care

Abstract: The use of benzodiazepine anxiolytics and hypnotics continues to excite controversy. Views differ from expert to expert and from country to country as to the extent of the problem, or even whether long-term benzodiazepine use actually constitutes a problem. The adverse effects of these drugs have been extensively documented and their effectiveness is being increasingly questioned. Discontinuation is usually beneficial as it is followed by improved psychomotor and cognitive functioning, particularly in the elde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
147
0
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(162 citation statements)
references
References 79 publications
1
147
0
14
Order By: Relevance
“…However, a small intervention study in primary care showed that sending a letter from the physician to the BZD/Z user could have a positive impact on successful withdrawal [51,52]. Motivation and gradual tapering seems to be the best strategy for discontinuation [11,53].…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a small intervention study in primary care showed that sending a letter from the physician to the BZD/Z user could have a positive impact on successful withdrawal [51,52]. Motivation and gradual tapering seems to be the best strategy for discontinuation [11,53].…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…Long-term use of benzodiazepines is discouraged in guidelines [5,7,8] because of the lack of effectiveness after 4 weeks [9,10], the increased risk of dependence and abuse, and withdrawal syndromes [11,12]. Moreover, it has been hypothesised that long-term use might have a detrimental effect on cognition and a potential acceleration of cognitive impairment [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Ved uttalte plager kan det i enkelte tilfeller vaere aktuelt å bruke et adjuvant legemiddel for en periode for å redusere symptomene. Klonidin ved opioidnedtrapping og karbamazepin og antidepressiver ved seponering av benzodiazepiner er eksempler (6). Oppfølging fra for eksempel fastlege med ikke-medikamentelle tiltak med vekt på støtte og motivasjon er effektive og lite ressurskrevende tiltak som øker sjansen for å lykkes med nedtrapping (7).…”
Section: Seponeringssyndromunclassified
“…Já no Canadá e na Espanha, estes são utilizados por mais de 20% dos idosos e, na Austrália, prevalece o seu uso em cerca de 15% (CARRASCO-GARRIDO et al, 2007;HOGAN et al, 2003;WINDLE et al, 2007) Atualmente, apesar desta prática de utilização apresentar-se menos acentuada nos EUA e no Reino Unido, verifica-se uma escala ainda elevada em idosos (GALLACHER et al, 2012). Fator este em modificação, principalmente nos países da Europa, em virtude de programas governamentais de conscientização aos profissionais envolvidos no atendimento ao paciente para promoção de descontinuação acompanhada desta classe farmacológica, visando minimizar os efeitos de abstinência até a sua total extinção (GOULD et al, 2014;HARTHOLT et al, 2011;LADER et al, 2009;SALONOJA et al, 2012;VELERT VILA et al, 2012).…”
Section: Em 2005 Foi Desenvolvido O "Ii Levantamento Domiciliar Sobrunclassified
“…As incidências de eventos adversos relatados no grupo flunitrazepam foram vertigem (4), depressão (10), artralgia (5), diarreia (6), dor de cabeça (6); no grupo zopiclona, foram relatados vertigem (10), depressão (7), artralgia (7), diarreia (2), dor de cabeça (2) e; no grupo placebo inicial (n=102), vertigem (3), depressão (6), artralgia (6) Com relação às perdas e desistências, um paciente faleceu durante o estudo devido a infarto de miocárdio, apresentando histórico prévio e fumante. Dezoitos pacientes, durante a fase de randomização duplo-cega, desistiram do estudo devido à eventos adversos, sendo dois do grupo zolpidem, cinco do triazolam (dor de cabeça, letargia, dor no peito, diarreia e sonolência), 5 do temazepam (tontura, asma, vertigem, amebíase e acidente automobilístico) e 6 do grupo placebo (dor na virilha, bursite, fratura de quadril, infecção de ouvido, sonolência e náusea).…”
Section: Características Metodológicas E Dados Descritivos Dos Estudounclassified